Analisis Efektivitas Bantuan Sosial (Bansos) dalam mengatasi Kemiskinan di Indonesia - Salsabila, Nanda; Muna, Nilna; Pradana, Vikko Hilmi; Nurcahya, Wirawan Firman (Indonesian Journal Publisher, 2024)
This study aims to analyze the effectiveness of the influence of social assistance in overcoming poverty in Indonesia. The poverty rate in Indonesia has reached an alarming number so that the government has issued various social assistance to ease the burden on the poor, but in reality, many distributions of social assistance are not on target. The method used in this study is a library study with secondary data obtained from various sources including literature, research reports, and official government documents relevant to this topic. The results of this study indicate that social assistance issued by the government is less effective in eradicating poverty in Indonesia, but the government needs to continue the social assistance program so that it can help the burden of poor families and reduce the number of poor people in Indonesia. Of the various social assistance issued by the government, the Family Hope Program (PKH) is one of the social assistance programs that is considered effective in helping to realize community welfare. The main obstacles that make the achievement of this social assistance less than optimal are inaccurate data on prospective recipients, political interests that target the poor, and limited evaluation. The distribution of social assistance needs to be improved, a more comprehensive program is needed, as well as structured synergy and coordination between all officers and stakeholders so that social assistance can help the poor people who should be the target in order to be able to free the poor from poverty.